Exploring regional differences in religiosity among Muslim youth in Malaysia - Krauss, Steven Eric; Hamzah, Azimi; Suandi, Turiman; Mohd Noah, Sidek; Juhari, Rumaya; Manap, Jamiah; Mastor, Khairul Anwar; Kassan, Hasnan; Mahmood, Azma (Religious Research Association, 2006)
Despite strong evidence of regional differences in religiosity levels in the U.S. (Stump 1986; Chalfant and Heller 1991), attempts to compare these findings with those of populations outside the U.S., and with non-Christian adherents, have been scant. Among Muslims and Muslim countries in particular, little known research has been conducted looking at regional differences in religiosity. In Malaysia, a predominantly Muslim nation, less modernized rural areas are considered by many to be more religiously and culturally traditional than urban areas (EASCAP 2002). Despite common perceptions about the differences in religiosity among rural and urban youth that are reflective of the dramatic differences in lifestyle and culture of the two regions, to date no known formal attempt has been made to uncover differences in religiosity between rural and urban Muslim youth. The current study aimed to address this gap by comparing religiosity among young Muslims from urban and rural areas of Malaysia, utilizing a multi-dimensional religiosity model and scales developed specifically for the Malaysian Muslim community (The Muslim Religiosity- Personality Inventory, or MRPI). Findings indicated significantly higher levels of religiosity for rural Muslim youth than their urban counterparts across all of the religiosity variables. The findings are significant for the formulation of Islamic education and practice strategies for the promotion of positive behavioral and moral development among Malaysian Muslim youth.